2021
DOI: 10.13005/bpj/2156
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2, MMP-9, TNF-α Levels in Relation to Sub types of Attention Deficit Hyperactivity Disorder

Abstract: Many authors have suggested the association between Attention Deficit Hyperactivity Disorder (ADHD) and inflammation through various mechanisms among which increased serum cytokines.30 newly diagnosed ADHD children, aged 6-12and of both sexes were collected from outpatient clinic, Psychiatry Department, Al Zahraa University Hospital and a matched control group of 30 children. They were subjected to Clinical assessment, Whechsler Intelligence Scale for children (WISC), Conners' Parent Rating Scale-Revised &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, one pro-inflammatory cytokine, TNF, showed contradictory effects on ADHD impulsivity in different studies. Serum TNF levels had a positive correlation with impulsivity [15,16]; yet Chang and colleagues found that youth with ADHD had a lower level of TNF, using meta-analysis [17]. Elevated levels of serum TNF levels indicate the activation of systemic immune responses, which might induce neuroinflammation leading to behavior changes [18].…”
Section: Inflammatory Impulsive Adhdmentioning
confidence: 99%
“…However, one pro-inflammatory cytokine, TNF, showed contradictory effects on ADHD impulsivity in different studies. Serum TNF levels had a positive correlation with impulsivity [15,16]; yet Chang and colleagues found that youth with ADHD had a lower level of TNF, using meta-analysis [17]. Elevated levels of serum TNF levels indicate the activation of systemic immune responses, which might induce neuroinflammation leading to behavior changes [18].…”
Section: Inflammatory Impulsive Adhdmentioning
confidence: 99%
“…In contrast, Cortese et al 21 found a signi cant positive correlation between IL-6 and TNF-α with hyperactive-impulsive ADHD in children and adolescents with ADHD and obesity. Others found that TNF-α levels correlated positively with inattention symptoms 22 . Together these results have so far been unable to establish a clear association between ADHD speci c behaviour and in ammatory proteins.…”
Section: Introductionmentioning
confidence: 99%